A literacy voyeur. “The CAT“ by Juan García Ponce - Buendía, Maritza M. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Since some years ago, the hermeneutics of Paul Ricoeur has been worked, studied, and spread in Mexico, especially by Doctor Gloria Prado, which can be noted in her book “Creation, Reception and effect. A hermeneutic approximation to the literary work” (1992), as well as her article titled “Neohermeneutics and Literary Theory. Literature, philosophy and other disciplines” (2009). In both writings, Prado establishes five hermeneutic levels as a method of literary analysis which permits the identification of the symbolic texture of a text. Starting from here, in hand with Ricoeur and Prado, and without leaving to the side the dialogue with other thinkers José Ortega and Gasset, Hans George Gadamer and Pierre Klossowski, I propose to conduct a hermeneutic analysis of the story, “The Cat”, (published in 1972 in “Encounters”), from the Mexican writer, Juan García Ponce, located in the named Half Century Generation: the generation which in its majority, is influenced by the work of Octavio Paz and George’s Bataille.